PENERAPAN TEKNIK PERIODIC ACID SCHIFF (PAS) PADA DIAGNOSIS HISTOPATOLOGI - Fajriza Yona; Salmiah Agus; Tofrizal Tofrizal (LPPM Universitas Abdurrab, 2022)
Histopathological tissue examination with routine staining sometimes cannot provide a clear morphology of certain cells or tissues, therefore special staining techniques based on histochemical reactions are needed. Periodic Acid-Schiff's (PAS) is a histochemical staining method specifically used to detect the presence of polysaccharide carbohydrates, neutral mucins and other glycoproteins. This article was written with the aim of increasing knowledge for practitionersor clinicians regarding the PAS technique procedure and how it is used in diagnosis. The method of writing scientific papers is a literature review sourced from various journals, books and scientific articles that are relevant and in accordance with the topics discussed. The PAS technique procedure begins with fixation in 10% neutral buffer formalin, preparation of materials and reagents, PAS staining with counterstain and interpretation. The addition of diastase was performed before PAS stain for PAS/D, and Alcian Blue staining was performed before PAS stain for the AB/PAS technique. Errors at each stage will affect the results of PAS staining. The use of combined PAS and PAS techniques in pathological diagnosis is to exclude the differential diagnosis of various tumors containing glycogen and mucin, examine the thickness of the basement membrane in various diseases, and identify Jamur and amoeba in tissue infections.